Lifetime Devotion to Ethnology - Paukštytė-Šaknienė, Rasa (Tautosakos darbai, 2019)
The 100th anniversary of a renowned Lithuanian ethnologist – professor Angelė Vyšniauskaitė (1919–2006) was widely celebrated by the Lithuanian academic community. Professor has dedicated all her life to promoting the Lithuanian ethnology: she worked at the Lithuanian Institute of History (in its Department of Ethnology) for more than four decades (1948–1993), writing books, editing collections, supervising dissertations and generously sharing her professional advice with colleagues and students. Her main research interests included Lithuanian family customs, community and calendar traditions, as well as regional and local culture, and Lithuanian historiography. She also published on agricultural traditions, particularly those related to flax growing, and traditional architecture. She was actively engaged in pedagogic activities (entire generation of contemporary ethnologists and folklorists are proud to be able to call her their teacher and advisor), and various social initiatives related to fostering traditional ethnic culture. In 1998, Professor Angelė Vyšniauskaitė was awarded the prestigious national Jonas Basanavičius’ Prize.
Keywords: -